Calculations of additional axial force and coupling ratio for coupled shear walls. (January 2023) - Zhang, Lingxin; Liu, Tao; Chen, Yongsheng
Highlights: Calculation formulas of additional axial force (AAF) and coupling ratio (CR) for coupled shear walls under lateral loads are proposed with detailed derivation. The AAF calculation formulas are derived by establishing and solving a differential equation about itself with concise expressions of external moment. CR formulas are theoretically derived based on AAF calculation formulas and are applied to simplify the formulas of top lateral deflection for coupled shear walls. The high accuracy and efficiency of the AAF and CR calculation formulas are revealed by comparison with numerical simulations and existing methods. Abstract: The additional axial forces (AAFs) in walls and coupling ratio (CR) of coupled shear wall (CSW) systems have significant effects on the local behaviors of the individual walls and the overall structural performance, respectively. A new analytical approach to obtaining AAF and CR for three different types of lateral loads has been proposed to avoid complex numerical simulations or time-consuming analyses. Firstly, a differential equation with respect to AAF was established using a concise expression of the external moment; AAF calculation method considering triangular, uniform, and top concentrated lateral loads was developed. Secondly, CR calculation formulas for three different types of lateral loads were derived based on the formulas of AAF and applied to simplify the formulas of calculating top lateral deflection of CSWs. Thirdly, the calculation method of AAF, CR and the simplified formulas of top lateral deflection were validated by conducting numerical simulations using ABAQUS and OpenSees. Finally, the advantages of the proposed methods as well as the impact of lateral load types and nonlinearities, etc. were discussed. It was found that AAF and CR could be efficiently calculated by the proposed approach for CSWs including asymmetric ones subjected to three typical lateral loads, and the relative errors compared with numerical simulation are less than 10%. Besides, different types of lateral loads affect the distributions of AAFs and the values of CR.